Lampyrids recovered from emergence traps in the Great Smoky Mountains National Park - Buschman, Lawrent L.; Faust, Lynn F. (My University, 2014)
Photinus carolinus Green is a popular firefly that attracts thousands of visitors each year to the Great Smoky Mountains National Park (GSMNP) (Faust, 2009). This firefly is famous for its synchronous flash display in late May and June. The adult flash behavior of this firefly was described by Lloyd (1966) and the synchronous flash behavior was further detailed by Copeland and Moiseff (1995) and Faust (2009, 2010). The biology and natural history of this insect was reported by Faust (2010). This firefly is dependent on larval feeding for its nutrition (adults are nonfeeding), but we know little about the seldom seen larval stage. Rearing has repeatedly proved difficult. For instance, though Buschman (1977) was able to record field and some laboratory observations on field collected larvae, only 2 of the original 59 Photinus consimilis Green complex larvae (closely related to P. carolinus) were successfully reared to adulthood (unpubl. obs.). These larvae were found in marshy habitat feeding on small annelids (Buschman, 1977). Some 40 yr later the biology and natural history of larval Photinus spp. remains poorly understood. This study was done to determine if the fireflies were emerging from the soil/leaf litter in the firefly habitat. This information on larval habitat will be important for understanding the conservation, survival and/or maintenance of fireflies like P. carolinus. It could also support the hypothesis that they are feeding on earthworms and/or other organisms in the soil and leaf litter.
Citation: Buschman, L. & Faust, L. (2014). Lampyrids Recovered from Emergence Traps in the Great Smoky Mountains National Park. JOURNAL OF THE KANSAS ENTOMOLOGICAL SOCIETY, 87(2), 245-248. https://doi.org/10.2317/JKES130409.1
Keywords: Photinus carolinus Green; Great Smoky Mountains National Park; Firefly; Larval habitat